« Used » Landscape’s Cultural Heritage Contra « Virgin » National Nature - Kenneth R. Olwig (Revue d'ethnoécologie)
Conservation, whether it be of landscape or nature, is necessarily rooted in human culture, because the perception of what is landscape, and what is nature, and why a given landscape or area of nature is important, is a human judgment. This article focuses on the cultural idea of heritage, and its role in determining why certain landscapes, conceptualized as being « natural », are conserved. It argues that « used », as opposed to « virgin », landscapes have a particular appeal because they have been preserved from generation to generation as a form of common inheritance that individuals do not own, but « merely look after it for the next generation ». To illustrate the point it takes its point of departure in a highly successful watch advertisement that uses this phrase as its slogan.